Formulation and Characterization of Cinnarizine Targeted Aural Transfersomal Gel for Vertigo Treatment: A Pharmacokinetic Study on Rabbits - Abdelmonem R (Dove Medical Press, 2020)
Rehab Abdelmonem,1 Raghda Rabe Hamed,1 Sally A Abdelhalim,2 Mohamed F ElMiligi,1,2 Mohamed A El-Nabarawi2 1Department of Industrial Pharmacy, College of Pharmaceutical Science and Drug Manufacturing, Misr University for Science and Technology, Cairo, Egypt; 2Department of Pharmaceutics, Faculty of Pharmacy, Cairo University, Cairo, EgyptCorrespondence: Rehab AbdelmonemDepartment of Industrial Pharmacy, College of Pharmaceutical Science and Drug Manufacturing, Misr University for Science and Technology, Al-Motameyez District, 6th October City, Giza, EgyptTel +20 1222127127Email drrahoba@yahoo.comIntroduction and Aim: Cinnarizine is indicated orally for treating vertigo associated with Ménière’s syndrome and has a local anesthetic effect as well. The present study aims to develop an aural Cinnarizine mucoadhesive transfersomal gel to overcome the first-pass metabolism.Methods: Eighteen Cinnarizine transfersomes were prepared by the thin-film hydration technique using different types of phosphatidylcholine and edge activators in different ratios. Formulae were tested for their appearance, entrapment efficiency, and in-vitro drug release after eight hours. F1, F4, F7, F9, F10, and F12 were selected to be examined for particle size, polydispersity index, and zeta potential. According to the previous parameters, F1 and F10 were incorporated into gels using different polymers according to factorial design 23. The eight gels were tested for appearance, pH, mucoadhesion, spreadability, drug content, in-vitro drug release after eight hours, and rheology. The transfersomal gel F1A was subjected to FTIR analysis and in-vivo pharmacokinetic study.Results: The transfersomal dispersion colors were ranging between the white and yellow. Their EE % ranged from 64.36± 1.985% to 94.09± 1.74%, and their in-vitro release percentages were between 61.82± 1.92% and 95.92± 1.18%. Also, the vesicles PS ranged from 212.3± 30.05nm to 2150± 35.35nm, DI from 0.238± 0.134 to 1± 0.00 and zeta potential from − 57.5± 2.54 to +4.73± 1.57 mV. The transfersomal gels showed pseudoplastic behavior, pH range of 5.5 to 8, a mucoadhesive force of 169.188± 1.26 to 321.212± 6.94 (dyne/cm2× 102), spreadability of 40 ± 7.03mm to 138 ± 3.77mm, and in-vitro drug release of 81.63± 1.128% to 97.78± 0.102%. The IR spectra of the (drug-excipients) physical mixture revealed that there were no shifts of incompatibility. The in-vivo pharmacokinetic study illustrated that [AUC]0– 24 of F1A was significantly higher than that of tablets at (P< 0.05), equivalent to 703.563± 26.470 and 494.256± 9.621ɲg.hr/mL respectively.Conclusion: The study revealed that Cinnarizine aural mucoadhesive targeted delivery provides an improved systemic bioavailability over the conventional oral route.Keywords: targeted transfersomes, aural gel, Cinnarizine